Hypnotherapy with nocturnal enuretic boys - Edwards, Stephen David (Department of Psychology, 2016)
The main objective of the present study was to provide an adequately controlled experimental and clinical study to assess the efficacy of hypnotherapy in the treatment of nocturnal enuresis. Hypnotherapy was operationally defined in terms of current research in hypnosis. Subjects were 48 nocturnal enuretic boys, aged 8 to 13. Treatment consisted of six standardised sessions, one hourly session per subject per week. Results indicated that hypnotherapy was significantly more effective in decreasing (a) nocturnal enuresis, compared with both pretreatment base line enuresis frequency and a no treatment control (b) maladjustment. Secondary enuretics were found to be more maladjusted than primary enuretics, responded better to hypnotherapy, yet relapsed more after treatment. Comparisons with other studies indicated that hypnotherapy was a desirable short term clinical alternative to more established psychotherapeutic, psychopharmacological and conditioning methods of treatment.